1986
DOI: 10.1159/000242558
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Digoxin-Like Immunoreactivity and Electrolyte Values in Urinary Samples of Newborns

Abstract: Elevated levels of a group of substances with digoxin-like immunoreactivity (DLIS) are present in biological fluids of newborns. These endogenous substances could also have the biological properties of cardiac glycosides, such as natriuretic and vasoconstrictor activity. Therefore, DLIS could be involved in electrolyte and volume regulation in infants. We measured DLIS, electrolyte (Na+, K+, Cl––) and creatinine concentrations in 157 urine samples collected from full-term and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…With [21] have already demonstrated that creatinine concentration correlated significantly with EOLS in 142 urine samples collected from preterm and full-term neonates.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…With [21] have already demonstrated that creatinine concentration correlated significantly with EOLS in 142 urine samples collected from preterm and full-term neonates.…”
Section: Discussionmentioning
confidence: 92%
“…Studies in the perinatal period have re vealed tissue distribution of EOLS with the highest content in the fetal/neonatal adrenals followed by the gut and the brain [13,14] and there have been reports indicating that plas ma levels and urinary excretion of EOLS inversely correlate with gestational and post natal ages [15][16][17][18], Moreover, significant pos itive correlation has been found between neo natal EOLS and fractional sodium excretion implying that EOLS might be involved in sodium and volume regulation during the ear ly postnatal life [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma DLIS levels were related with creatinine levels in adult [16], pediatric [43], and neonatal studies [44]. However, no correlation was found between the DLIS and creatinine levels of adult cases with renal insufficiency [45].…”
Section: Discussionmentioning
confidence: 99%